Spanish translation and analysis of the metric properties of inpatient satisfaction scale in psychiatry: The Satispsy-22-E. (October 2018) - Frías, V.M.; Colom, F.; Bulbena, A.; Aceña, R.; Pratdesava, A.; Zendjidjian, X.Y.; Perez-Sola, V.
Highlights: The knowledge of the satisfaction level of the admitted patients is of great importance for the improvement of the quality of the sanitary services. Although there are a number of interesting articles regarding this topic, they do not focus on the inpatient perspective. The Satipsy-22-E shows good metric properties and it's a good tool available now in Spanish language, allowing learning more about inpatients' real needs. We hope this way we will all be able to improve our clinical practice. Some of the intervening variables are specific to psychiatric wards. Involuntary income, constraining and similar topics related to the restrictive measures of these wards produce a differential effect when evaluating the admission experience. Abstract: The Satispsy-22 scale is an instrument created for the specific evaluation of psychiatric inpatient satisfaction. Therefore, the study aims to carry out the Satispsy-22 scientific translation to Spanish and to learn its psychometric properties. The Satipsy-22-E was administered to discharged patients from four units of acute psychiatric admission, a unit of dual pathology and two units of subacute psychiatric admission ( N = 268). Cronbach's alpha was 0.886, which can be interpreted as good internal reliability. All the dimensions showed a good internal consistency with scores from 0.722 to 0.919. Test-retest offered scores of 0.752–0.951 showing good stability. Confirmatory factor analysis showed that all elements load in the estimated dimensions of the original scale and these were significant and the adjustment measures showed, in general, a rather good adjustment, Root Mean Square Error (RMSE) showed that the error between observations and actual data is small and acceptable. Satispsy-22-E is a specific scale in Spanish language for the assessment of psychiatric inpatient satisfaction. It is an easy to use tool that offers good psychometric properties. The availability of a validated survey in Spanish may help to improve the care provided by psychiatric wards in Spanish-speaking countries.